Akumulasi logam besi (Fe) pada tumbuhan air di sungai Sebangau, Kalimantan Tengah - Bambang Sulistiyarto (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
The aim of this study was to select aquatic plants in Sebangau river that has ability to absorb Iron (Fe) from waters. The Concentration of Fe in the roots and leaves of aquatic plants were measured using AAS (atomic absorption spectrophotometer). The results showed that the highest accumulation of Fe was in Hanguana malayana root which reached 36967.93 ± 20951.50 mg/Kg or 3.53 times of Fe concentration in Pandanus helicopus root and 3.26 times of Echinocloa stagnina root. Echinocloa stagnina has the highest Fe transfer factor reaching 0.0224 and has potential for phytoremediation of Fe. Key words : Iron (Fe), Aquatic plants, Sebangau river, peat waters, phytoremediation.